Development of Seed Butter Made with Pumpkin, Sesame, and Sunflower Seeds and the Influence of Natural Antimicrobials and Stabilizers on Its Shelf Life - Yung-Hsin Chien; Melvin A. Pascall (International Journal of Food Science)
This study investigated the antimicrobial efficacies of grape seed extract (GSE) and cinnamaldehyde (CIN) against Salmonella enterica and Listeria innocua and the influence of hydrogenated rapeseed oil (HRO) and palm kernel oil (PKO) on the texture and oil separation in pumpkin/sesame/sunflower seed butter. The results showed that the 10 and 15% GSE significantly reduced both S. enterica and L. innocua. Cinnamaldehyde was effective against S. enterica but did not significantly reduce L. innocua. Hydrogenated rapeseed oil at 2 and 3% concentrations prevented hardening of the seed butter and thus facilitated its spreadability. The 3% HRO-stabilized seed butter had less oil separation and a better texture than the control. Although PKO influenced the hardness of the butter after 35 days, its effect was not as pronounced as that of HRO. The HRO was also more effective in reducing the adhesiveness and thus the stickiness of the seed butter when compared with the PKO. Both HRO and PKO did not influence cohesiveness and adhesiveness changes to the butter after 7 days, although the HRO samples showed a lower level of cohesiveness when initially added to the samples.